Pengaruh Perilaku Konsumen Dan Media Sosial Terhadap Minat Beli Merchandise K-Pop Di Bandung - Mulyasari, Rosi; Somadi (CV. SINAR HOWUHOWU, 2025)
T The growing popularity of K-pop in Indonesia has influenced consumer behavior, especially in merchandise purchases. Despite high fan engagement on social media, actual buying interest remains inconsistent, indicating a research gap. This study investigates the impact of consumer behavior and social media on purchase intention of K-pop merchandise in Bandung. Using a quantitative approach with 100 K-pop fans and path analysis, results show that both variables significantly and positively affect purchase intention, both individually and simultaneously. These findings offer academic insights into Fandom-related consumer behavior and practical guidance for creative industries in popular culture.